Architecture of the crust and uppermost mantle in the northern Canadian Cordillera from receiver functions. Issue 7 (12th July 2017) - Tarayoun, Alizia; Audet, Pascal; Mazzotti, Stéphane; Ashoori, Azadeh
Abstract: The northern Canadian Cordillera (NCC) is an active orogenic belt in northwestern Canada characterized by deformed autochtonous and allochtonous structures that were emplaced in successive episodes of convergence since the Late Cretaceous. Seismicity and crustal deformation are concentrated along corridors located far (>200 to 800 km) from the convergent plate margin. Proposed geodynamic models require information on crust and mantle structure and strain history, which are poorly constrained. We calculate receiver functions using 66 broadband seismic stations within and around the NCC and process them to estimate Moho depth and P ‐to‐ S velocity ratio ( V p / V s ) of the Cordilleran crust. We also perform a harmonic decomposition to determine the anisotropy of the subsurface layers. From these results, we construct simple seismic velocity models at selected stations and simulate receiver function data to constrain crust and uppermost mantle structure and anisotropy. Our results indicate a relatively flat and sharp Moho at 32 ± 2 km depth and crustal V p / V s of 1.75 ± 0.05. Seismic anisotropy is pervasive in the upper crust and within a thin ( 10–15 km thick) sub‐Moho layer. The modeled plunging slow axis of hexagonal symmetry of the upper crustal anisotropic layer may reflect the presence of fractures or mica‐rich mylonites. The subhorizontal fast axis of hexagonal anisotropy within the sub‐Moho layer is generally consistent with the SE‐NW orientation of large‐scale tectonic structures. These results allow us to revise the geodynamic models proposed to explain active deformation within the NCC. Key Points: We constrain crust and uppermost mantle structure in the northern Canadian Cordillera using receiver functions Moho is sharp and flat at 32 ± 2 km, and we find upper crustal and sub‐Moho anisotropic layers likely related to Cordilleran evolution Lateral and vertical variations in seismic anisotropy allow revision of geodynamic models proposed to explain active tectonic deformation